Kritik ekologi cerpen “O” Karya Benny Arnas dalam Kompas 17 April 2022: Perspektif Greg Garrard - Nuni Anggraeni (Aksara: Jurnal Bahasa dan Sastra, 2023)
The development of the oceans is now starting to be threatened due to climate change and ecosystem imbalances that occur in nature. It is important for us as the nation's successors to preserve and cultivate the surrounding environmental ecosystem for a better environment. This study aims to examine the wisdom of the sea through the behavior and thoughts of the characters in the short story “O” by Benny Arnas using a descriptive qualitative method. The research data source comes from kompas.id with a short story entitled "O" by Benny Arnas in 2022. The analysis technique is based on the theory of ecocriticism. The analysis is carried out by reading the short stories repeatedly to find sentences that contain ecological wisdom. The results of the research found ideas in uncovering the phenomenon of the marine coastal environment, namely planting fruits and vegetables in the coastal areas of the sea. The short story entitled "O" by Beny Arnas describes the concern for the health of the people of the Karimata sea coast. Changes in awareness of the marine environment need attention for people who are less willing to take risks. With figure O the research found an overview of ideas in uncovering marine environmental phenomena, namely planting fruits and vegetables in seacoast areas. Suggestions in this paper, readers are expected to be wiser in treating the natural environment around them.Keywords: Ecocriticism, Short Stories, Marine Environment